Электронное правительство как технология государственного управления (сравнительный анализ) (Էլեկտրոնային կառավարությունը որպես պետական կառավարման տեխնոլոգիա (համեմատական վերլուծություն)) - Անտանովիչ Նինա (YSU Journal of International Affairs, 2017)
In the article, SWOT-analysis was used to assess the role of e-government as a tool in Public Administration. Transformation of egovernment was studied according to the UN Global e-government Surveys. A comparative analysis of the evolution of electronic government as the Public Administration technologies on the example of the E-Government Development Index, E-Participation Index of the Russian Federation, Republic of Kazakhstan, the Republic of Armenia, Belarus and Ukraine was done. On the basis of the comparative analysis, the author makes a conclusion that the trend of e-government development is the provision of electronic services, providing online transaction and feedback from citizens to government institutions which make their activities more open and transparent.